The Cyclops: Portrait of an Ogre - Aguirre, Mercedes (The Biblical archaeology review, 2022)
Few characters from Greek mythology echo in the mind as resonantly as Polyphemus, the one-eyed, cave-dwelling, human-eating, sheep-and-goat-herding ogre outwitted by the hero Odysseus on his voyage homewards from Troy to Ithaca. As unforgettably recorded in Homer’s epic poem the Odyssey, this episode involves a succession of key moments: Polyphemus’s imprisoning of the Greek […]